Generating equilibrium dark matter halos: Inadequacies of the local Maxwellian approximation - Kazantzidis, S; Magorrian, J; Moore, B (Institute of Physics Publishing, 2004)
We describe an algorithm for constructing N-body realizations of equilibrium spherical systems. A general form for the mass density ρ(r) is used, making it possible to represent most of the popular density profiles found in the literature, including the cuspy density profiles found in high-resolution cosmological simulations. We demonstrate explicitly that our models are in equilibrium. In contrast, many existing N-body realizations of isolated systems have been constructed under the assumption that the local velocity distribution is Maxwellian. We show that a Maxwellian halo with an initial ρ(r) ⊥ r-1 central density cusp immediately develops a constant-density core. Moreover, after just one crossing time the orbital anisotropy has changed over the entire system, and the initially isotropic model becomes radially anisotropic. These effects have important implications for many studies, including the survival of substructure in cold dark matter (CDM) models. Comparing the evolution and mass-loss rate of isotropic Maxwellian and self-consistent Navarro, Frenk, and White (NFW), satellites orbiting inside a static host CDM potential, we find that the former are unrealistically susceptible to tidal disruption. Thus, recent studies of the mass-loss rate and disruption timescales of substructure in CDM models may be compromised by using the Maxwellian approximation. We also demonstrate that a radially anisotropic, self-consistent NFW satellite loses mass at a rate several times higher than that of its isotropic counterpart on the same external tidal field and orbit.